Reproductive Systems in Paspalum: Relevance for Germplasm Collection and Conservation, Breeding Techniques, and Adoption of Released Cultivars - Acuña, Carlos A.; Martínez, Eric J.; Zilli, Alex L.; Brugnoli, Elsa A.; Espinoza, Francisco; Marcón, Florencia; Urbani, Mario H.; Quarin, Camilo L. (Frontiers in Plant Science, 2019)
The objective of this review is to analyze and describe the impact that mode of reproduction in Paspalum has on germplasm conservation, genetic improvement and commercialization of cultivars. Germplasm collection and conservation can now be rethought considering the newly available information related to how diversity is allocated in nature and how it can be transferred between the sexual and apomictic germplasm using novel breeding approaches. An inventory of species and accessions conserved around the world is analyzed in relation to the main germplasm banks. Because of the importance of apomixis in Paspalum species different breeding approaches have been used and tested. Knowledge related to the inheritance of apomixis, variable expressivity of the trait and techniques for early identification of apomicts has helped to improve the efficiency of the breeding methods. Novel breeding techniques are also being developed and are described regarding its advantages and limitations. Finally, the impact of reproductive mode on the adoption of the released cultivars is discussed.